Resistência a inseticidas organofosforados e carbamatos em população de Culex quinquefasciatus Organophosphorous and carbamate resistence in a population of Culex quinquefasciatus - José Eduardo Bracco; Moacyr Dalbon; Osvaldo Marinotti; José Maria Soares Barata (Universidade de São Paulo, 1997)
Relata-se a ocorrência, na população de Culex quinquefasciatus, de resistência a pelo menos dois organofosforados e a um carbamato (malathion, fenitrothion e propoxur, respectivamente), mostrando a necessidade de haver programa de manejo de inseticidas. A suscetibilidade dessa população ao piretróide permetrina indica essa classe como de escolha numa eventual necessidade de substituição dos organofosforados. The population of Culex quinquefasciatus breeding in the Pinheiros River (S. Paulo, Brazil) has been controlled with organophosphates since 1980. However, the biting has constituted a continual nuisance to the human population who live in the vicinity of the river. The occurrence of insecticide resistance to at least two organophosphates and one carbamate (malathion, fenitrothion and propoxur, respectively) to this insect population is reported. The results show the need to develop an insecticide management program. The suscetibility to permethrin (pyretroid) suggests the possibility of using this class of insecticide shoul the need for replacement of the insecticide in use arise.